2013
DOI: 10.1371/journal.pone.0069460
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Allodynia – Evidence of Increased Pain Sensitivity in Healthy Humans and Patients with Chronic Pain after Experimentally Induced Psychosocial Stress

Abstract: BackgroundExperimental stress has been shown to have analgesic as well as allodynic effect in animals. Despite the obvious negative influence of stress in clinical pain conditions, stress-induced alteration of pain sensitivity has not been tested in humans so far. Therefore, we tested changes of pain sensitivity using an experimental stressor in ten female healthy subjects and 13 female patients with fibromyalgia.MethodsMultiple sensory aspects of pain were evaluated in all participants with the help of the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
99
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 62 publications
(54 reference statements)
7
99
2
Order By: Relevance
“…The notion that strictly psychological factors (eg, stress) can produce central sensitization is a relatively newer concept. For example, psychosocial stress produces allodynia in both healthy humans and fibromyalgia patients (Crettaz et al, 2013). Rodents exposed to restraint stress, swim stress, single prolonged stress (restraint+swim), unpredictable sound stress, or social defeat stress exhibit mechanical and thermal hyperalgesia that may be mediated by a combination of brain, spinal, and nociceptor mechanisms (Dina et al, 2011;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The notion that strictly psychological factors (eg, stress) can produce central sensitization is a relatively newer concept. For example, psychosocial stress produces allodynia in both healthy humans and fibromyalgia patients (Crettaz et al, 2013). Rodents exposed to restraint stress, swim stress, single prolonged stress (restraint+swim), unpredictable sound stress, or social defeat stress exhibit mechanical and thermal hyperalgesia that may be mediated by a combination of brain, spinal, and nociceptor mechanisms (Dina et al, 2011;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Study done on 26 opera singers to assess the acute stress response before, during and after a performance and founds the same increased PPT (3) Another study founds that hypersensitization plays a part in many chronic pain disorders such as fibromyalgia syndrome (fms), which has been associated withsubstantial decrease in pain threshold (25,26) Some studies showing the result that there are some changes occure at the cns level 18,19,20 ,21 ,27and there is overactivation of the hormonal stress-response system as a result of ongoing strain often leads to adown-regulated adrenocortical responsiveness characterized by relative primary adrenal hypocortisolism with increased feedback inhibition of the hpa axis. Maixner shows relation between sensitivity of patients with painful temporomandibular disorders to experimentally evoked pain (32) It has been shown that anxiety exacerbates pain through activation in the hippocampus (33) Quintero et aldemonstrated that hyperalgesia due to an inescapable subchronic stress is resulted from diminished central 5-HT activity (35 ) Chronic stress has been shown to attenuate dopaminergic activity in the nucleus accumbens, resulting in hyperalgesia (34)A study using positron emission tomography (PET) showed that psychological stress in humans causes mesolimbic dopamine release(36)Using pain as the stressor, another PET study showed that basal ganglia dopaminergic activity is involved in pain processing, as well as emotional processing of the pain stimulus (37)Nigrostriatal D2 dopamine receptor activity was related to the sensory aspect of pain, whereas mesolimbic D2/D3 dopamine receptor activity was related to negative affect and fear.…”
Section: Discussion :mentioning
confidence: 94%
“…In this study, 30.23% of the individuals were diagnosed with this dysfunction. It is highlighted that TMD has multifactorial etiology, being stress as one of the predisposing factors 1,19 .…”
Section: Discussionmentioning
confidence: 99%
“…A study found high prevalence of headache among the nursing team thought to be associated with occupational stress 30 . Although the development and evolution of headache can be influenced by stress 19 , it may not be the exclusive causing agent. The sample of this study is composed by women, and they are more susceptible to headache 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation